The Effectiveness Of Infographics Towards Students’ Reading Comprehension - Dody Wahyudi Purnama; Sari Lestari (Departement of Mathematics Education, 2023)
The aims of this research are (1) to find out how to apply infographics towards students' reading comprehension; (2) to find out the effect of using infographics as learning media towards students‟ reading comprehension; (3) to find out students' respond to the use of infographics as learning media. This research method is quantitative with a pre-experimental research design type of one-group pretestposttest design. The instruments in this study were tests, questionnaires, and observations. The test consists of a pretest, which is a test before being given treatment, and a posttest, which is a test after being given treatment. The treatment in this study is the application of infographics as learning media in procedure text. The results show that (1) the application of infographics can be applied to a text to clarify the contents of the text because it is supported by the visual elements of the infographics. The application of infographics in this study is to apply infographics to procedure text. The procedure text is presented in infographic form supported by illustrations and visual elements on infographics. (2) there is an effect of using infographics as learning media towards students' reading comprehension. It can be seen from the results of the paired sample test. With the significant value or Sig. (2-tailed) is 0.00 which is less than 0.05 it means that Ha is accepted. Another analysis of the paired sample test by comparing the t-test with the t-table, where ttest > t-table is 9.724 > 2.093 it means that Ha is accepted. Supported by the pretest-posttest results, can be seen from the difference in pretest and posttest values where the pretest has a mean of 34.75 and the posttest has a higher value of 63.757. (3) there was a good response from students towards the use of infographics as learning media. Students gave a positive response from the use of infographics as an effective medium in helping reading comprehension. This can be seen from the percentage (80%) of students agreeing with the statements in the questionnaire “I feel infographics can help me understand the text”. Supported by the results of observations with an average of 98%, it can be interpreted very good. Based on the analysis, it can be concluded that infographics are an effective learning media towards students'